The Teaching Using Visual Media and Achievement Motivation in Writing Skill: Pengajaran Menggunakan Media Visual dan Motivasi Berprestasi dalam Keterampilan Menulis - M Saleh Yahya Himni (Journal of Multidisciplinary Science, 2023)
The aim of this study was to investigate the effect of teaching by using visual media and achievement motivation on the student's writing competency. This study was conducted on the tenth-grade students of MA Hamzanwadi NW Pancor Lombok Timur. There were three variables in this study. Teaching using visual media (A) as the independent variable, achievement motivation (B) as a moderator variable, and writing competency (Y) as the dependent variable. This study was an experimental study with 2x2 factorial designs. The quantitative data were analyzed by using two-way ANOVA, which was continued by the Post-Hoc test by using the Tukey test. The output of this study showed that: 1) there is a significant effect of teaching by using visual media on the student's writing competency; 2) there is an interactional effect of teaching by using visual media and achievement motivation on the student's writing competency; 3) there is a significant difference on the student's writing competency between the groups were taught by using visual media with high achievement motivation and the groups were taught by using a conventional method with high achievement motivation; 4) there is no significant difference on the student's writing competency between the groups were taught by using visual media with low achievement motivation and the groups were taught by using the conventional method with low achievement motivation.